2016
DOI: 10.1055/s-0036-1586101
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Influenza Vaccination during Pregnancy on Birth Outcomes: A Systematic Review and Meta-Analysis

Abstract: Objective Numerous observational studies have evaluated the relationship between influenza vaccination during pregnancy and birth outcomes. The number of studies on this subject has increased, especially after the 2009 A/H1N1 pandemic (A/H1N1pdm09). This meta-analysis aims to determine the impact of maternal vaccination with either seasonal trivalent inactivated influenza vaccines (IIV) or A/H1N1pdm09 monovalent vaccines on the rates of preterm (PTB), small for gestational age (SGA), and low birth weight (LBW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 37 publications
4
64
1
1
Order By: Relevance
“…Our findings are consistent with a number of studies that found an association between receiving influenza vaccination and reduced likelihood of delivering a baby PTB or with LBW [16], [17], [18], [19], [20], [21], [22]. In addition, a recent meta-analysis found a strong association between receipt of influenza vaccination and reduced likelihood of PTB and LBW, and the magnitude of the association that Nunes et al reported was comparable to our findings [44].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with a number of studies that found an association between receiving influenza vaccination and reduced likelihood of delivering a baby PTB or with LBW [16], [17], [18], [19], [20], [21], [22]. In addition, a recent meta-analysis found a strong association between receipt of influenza vaccination and reduced likelihood of PTB and LBW, and the magnitude of the association that Nunes et al reported was comparable to our findings [44].…”
Section: Discussionsupporting
confidence: 93%
“…A study has shown the influenza vaccine also provided low‐to‐moderate protection against hospitalization with influenza virus infection . Reductions of 13% of preterm births and 26% of low birth weight were reported, but no effect on small for gestational age was reported . The safety of influenza vaccination during pregnancy was determined through post‐licensure vaccine safety monitoring platforms: pregnancy exposure registries; active and passive surveillance systems; and observational studies .…”
Section: Introductionmentioning
confidence: 99%
“…It is now established that influenza immunization during pregnancy reduces risk of influenza infection in pregnant women [8, 9]. Studies show no adverse effects of vaccination in relation to outcomes including, but not limited to, risk of preterm labor, C-section, or fetal malformation [1013]. …”
Section: Introductionmentioning
confidence: 99%